KEDUDUKAN DANA TABARRU’ DALAM ASURANSI SYARIAH - Syarifuddin Syarifuddin (IAIN Manado, 2017)
AbstractThe scientific article, discusses the fund position tabarru in Takaful. Issues raised is how to position the fund tabarru on Takaful. The aim is to analyze and understand the concept of funds tabarru, Islamic insurance and fund position tabarru in Takaful. This article, the normative research method conceptual approach. the result is that Takaful is a principled sharia financial institutions, funds tabarru part investment fund clients who deposited with financial institutions Takaful. Fund positions tabarru’ for Takaful is an Islamic insurance essence of existence that can not be separated. Keywords; Takaful, and funds tabarru’